Application of the Model Forest for conflict resolution in participatory management actions in the territory of Borborema-Paraíba, Brazil (Research, Society and Development, 2021)
One of the main characteristics of the Brazilian semiarid region is climate variability and water scarcity. Living with the semiarid region, even with all its naturalistic and cultural potential, is a challenge, due to the long periods of drought and the limitation of water resources. This study aims to adapt the Model Forest as a conflict solution methodology in participatory management actions in the territory of the Borborema Pole to strengthen coalitions and strategic measures of coexistence with the semiarid region. Therefore, the Bosque methodology was used as a model used to solve conflicts through a spatial or landscape cut of a scenario in environmental and social imbalance. Thus, the main results obtained through the application of the forest model were the various possible alternatives for conflict resolution through social mobilization with different interests and, consequently, the strengthening of measures aimed at mitigating the effects of the desertification process in a region with a shortage of natural resources and is experiencing a process of extinction in its biome, the Caatinga. It is therefore concluded that it was possible to obtain a better view of participatory management in the territory of Borborema. It should be noted that the possible conflicts that arise from different groups are also discussed as measures of the effectiveness of participatory management.